2020
DOI: 10.17953/aicrj.44.3.kalweit_etal
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Racial Misclassification in COVID-19 Mortality Data: The Role of Funeral Directors and Social Context

Abstract: Death certificates are a crucial tool in public health, yet American Indians and Alaska Natives have long been misclassified after death, most often as white. During the COVID-19 pandemic, rapid provisional death counts have used data from death certificates to identify outbreaks and allocate resources. This paper interrogates common practices of funeral directors—who complete the demographic portion of the death certificate—as well as the social context in which they operate. The paper then reviews how these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…The need for public health partnerships and resource provision with NA communities and organizations, including vaccine information and trusted messenger outreach efforts, supports previous findings from COVID-19 vaccine studies conducted with both NA and non-NA racial and ethnic minority populations [22] , [40] , [41] . Participants in our study articulated a need for increased unity in leadership and communication and expanded public health partnership, including financial and COVID-related resources and cultural tailoring, with NA networks to reach community members.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The need for public health partnerships and resource provision with NA communities and organizations, including vaccine information and trusted messenger outreach efforts, supports previous findings from COVID-19 vaccine studies conducted with both NA and non-NA racial and ethnic minority populations [22] , [40] , [41] . Participants in our study articulated a need for increased unity in leadership and communication and expanded public health partnership, including financial and COVID-related resources and cultural tailoring, with NA networks to reach community members.…”
Section: Discussionsupporting
confidence: 74%
“…Racial misclassification of NAs from other racial or ethnic groups and data omission have been an ongoing barrier to correctly identifying health disparities and policy changes that address these disparities [37] . NAs have also been prone to racial misclassification and omission in COVID-19 mortality data due to misclassification of race by funeral directors [40] . Data on COVID-19, including vaccination rates, may be captured by various health data systems, including tribal, state, county, and city health agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the US, information on race and ethnicity recorded on the death certificate is less accurate for nonwhite populations than for whites, a disparity partly due to inadequate training (12)(13)(14)(15)(16)(17)(18). Kalweit et al conducted surveys and interviews with funeral directors across the US.…”
Section: Problems In Decedent Race and Ethnicity Classification And D...mentioning
confidence: 99%
“…Kalweit et al conducted surveys and interviews with funeral directors across the US. They found that there is inconsistent training for funeral directors, and funeral directors do not follow standard methods for collecting and coding “Hispanic origin” and tribal affiliation on death certificates ( 18 ). NC funeral directors shared in informal interviews that they frequently report their own perceptions of the decedent's race without consulting next of kin.…”
Section: Problems In Decedent Race and Ethnicity Classification And D...mentioning
confidence: 99%
See 1 more Smart Citation